Metastatic colorectal adenocarcinoma in oral cavity: case report and Literature review - Pelissari, Cibele; Cavalcanti, Desiree; Braz-Silva, Paulo Henrique; Gallottini, Marina; Trierveiler, Marília (Journal of Oral Diagnosis, 2018)
Metastatic neoplasms of maxillary bones are rare and may exhibit symptoms of diseases of dental origin. The colorectal adenocarcinoma is one of the most common malignancies in the world and most predominantly metastasises to the liver and the lungs. We present a case report of metastatic colorectal adenocarcinoma in the mandible of a 64-year-old white female. The patient was referred to a stomatology service complaining of intense oral pain for 5 months. Her medical history revealed evidence of treatment for colorectal adenocarcinoma 3 years prior to this investigation. On clinical examination, a painful inflamed gingival overgrowth was discovered covering the space in which a tooth extraction had been undergone previously. To provide a diagnosis for this, biopsy and imaging studies were undertaken. Histology sections revealed a malignant neoplasm of glandular epithelial differentiation, characterized by proliferation of tall columnar neoplastic cells, organized in tubular structures of a single layer, characterizing metastatic colorectal adenocarcinoma. The patient received palliative chemotherapy but died of the disease 6 months after. In conclusion, despite the rarity of metastasis of the jaw, this condition should be considered and investigated, especially in patients with oral symptoms and history of malignancies